Sustainability Analysis of Oil Palm Plantations on Peatland in Rawa Bangun Village, Mukomuko Regency - Wulan Sari Ramadhanti; Ridha Rizki Novanda; Gita Mulyasari; Dian Adi Anggraini Elisabeth (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
Oil palm is a key commodity that significantly contributes to the economy of Rawa Bangun Village, where most of the population relies on oil palm farming. In this area, peatlands over 3 meters deep are utilized for oil palm plantations, often in degraded conditions with limited nutrient availability, posing challenges for cultivation. This study assesses the sustainability index and status of oil palm plantations on peatlands across five dimensions: economic, social, institutional, and technological, using the Multidimensional Scaling (MDS) method. The findings revealed a sustainability index of 57.26%, categorized as "Fairly Sustainable." The validity of this model is supported by a Squared Correlation (R²) value of 0.9576 (95.76%), indicating a strong correlation between dimensions and a stress value of 0.128, which falls within the acceptable error range (<0.25). Among the analyzed dimensions, the ecological, economic, social, and technological dimensions are classified as "Fairly Sustainable," while the institutional dimension is rated as "Less Sustainable." Sustainability can be enhanced through farmer training, improvements in FFB infrastructure, management of inter-farmer conflicts, increased FFB productivity and strengthened support for extension services through capacity building and integrated multi-stakeholder collaboration.